Efficient removal of selected fluoroquinolones from the aqueous environment using reduced magnetic graphene oxide/polyaniline composite. (April 2022) - Ullah, Tasbeeh; Gul, Kashif; Khan, Hamayun; Ara, Behisht; Zia, Tanveer Ul Haq
Abstract: In the present study, reduced magnetic graphene oxide/polyaniline (RmGO/PANI) composite was synthesized via in-situ oxidative polymerization method. The synthesized RmGO/PANI was characterized by fourier transform infrared, scanning electron microscope, X-ray diffraction and energy dispersive X-rays techniques. The synthesized RmGO/PANI was explored as an adsorbent for the removal of moxifloxacin (MOX) and ofloxacin (OFL) from the aqueous samples. To inflate removal efficiency of RmGO/PANI, various adsorption effecting parameters such as effect of pH (2-12), RmGO/PANI dosage (2–14 mg), analyte concentration (150–525 μg mL −1 for MOX and 15–40 μg mL −1 for OFL), contact time (10–120 min) and temperature (293–343 K) were studied. Moreover, kinetic study exhibits that adsorption of MOX/OFL using RmGO/PANI follows pseudo second order kinetic model. The adsorption of MOX/OFL well-fitted to the Langmuir adsorption isotherm which demonstrates mono-layer adsorption of MOX/OFL on the surface of RmGO/PANI with maximum adsorption capacity of 47.7 mg g −1 and 27.33 mg g −1 for OFL and MOX, respectively. Thermodynamic study indicates that the adsorption process was spontaneous and exothermic in nature with the decrease of randomness of the system during the adsorption. On account of its practical applications, RmGO/PANI is considered an excellent adsorbent with 99% and 96% removal efficacy for MOX and OFL, respectively. The synthesized RmGO/PANI was reused for ten consecutive batches as well as applied to the real samples, maintain an excellent removal capacity. The reusable nature of RmGO/PANI declare this solid medium as an innovative adsorbent for real sample applications and wastewater treatment. Graphical abstract: Image 1 Highlights: RmGO/PANI was synthesized by in-situ oxidative polymerization method. The composite has a promising high adsorption capacity for MOX and OFL. The adsorption equilibrium data followed Langmuir adsorption isotherm. The reusability extended to a limit of 10 consecutive cycles.